IMPLEMENTASI PERATURAN DAERAH NOMOR 8 TAHUN 2012 TENTANG RETRIBUSI GANGGUAN OLEH BPT-PM (STUDI KASUS PERIZINAN RUMAH MAKAN DI KECAMATAN BUKIT RAYA PEKANBARU) - Siti Ardianti; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Some problems caused by Restaurants in various cities are usually almost the same as the problem of congestion, cleanliness and the beauty of the city. This is because restaurants often tend to trade in places where they are not allowed to trade. Though buying and selling activities have been facilitated by the existence of a kiosk or permanent shelves and has met all the requirements to get the right as a market tenant whose rights are protected by law and safe from eviction.Research objectives: 1) To know and analyze the Implementation of Local Regulation No. 8 of 2012 on Levy Disturbance by BPT-PM (Case Study of Licensing Restaurant in Bukit Raya Pekanbaru Sub-district) 2) To know the obstacles that affect the Implementation of Local Regulation No. 8 of 2012 about Levy Disturbance by BPT-PM (Case Study of Licensing of Restaurants in Bukit Raya Pekanbaru Sub-district). Informants in this study are Head of BPT-PM Mr. Said Riza Fantoni ST, MT and Mr. Yausar as Head of Subdistrict Chief Bukit Raya, restaurant business actors, and representatives of buyers. Population used as informant because this research use qualitative research. Types and data sources use primary data, ie data obtained directly from respondents and secondary data, ie data obtained through reports, books and records. Techniques of collecting data using interviews, observation and documentation. Data analysis techniques by analyzing the data, then draw conclusions, and finally provide suggestions.Pursuant to result of research known Implementation of Regional Regulation of Pekanbaru City Number 8 Year 2012 About Retribution of Permit Of Disturbance Existing In Office Of Camat Bukit Raya done by doing Communication, Resource, Disposition, Bureaucratic Structure. The inhibiting factor that writer find in Implementation of Regional Regulation of Pekanbaru City Number 8 Year 2012 About Retribution Permit Existence In Office Bukit Raya Sub-district is communication, resources, disposition and Bureaucratic structure.Keywords: Implementation, Levy Disorders, Eating